Integrated Legal Supervision Model for Hospitals as Public Service Institutions in the Era of Health Decentralization - Rinaldi Pratama Musa; Rendi Saputra Harto; Muh. Zulkifli Nasir (Programs Study Outside the Main Campus in Law Pattimura University ARU Islands Regency, 2026)
This study aims to analyze the integrated legal supervision model of hospitals as public service institutions in the era of health decentralization. The approach used is normative legal research by examining various laws and regulations and the results of relevant previous research. The results of the study show that effective legal supervision requires synergy between the central government, local governments, accreditation institutions, and the community. Hospital accreditation plays a role as a legal instrument in ensuring the quality of service, while legal protection for patients of the Social Security Administration Agency (BPJS) is an integral part of the supervision of public services. Supervision that is not only administrative, but also substantive and educational, is necessary to prevent violations and ensure the hospital's legal responsibility. The proposed integrated surveillance model is expected to strengthen legal certainty, improve service quality, and realize social justice in the national health system.